TRANSFORMASI KEPATUHAN DALAM PROGRAM KELUARGA HARAPAN: STUDI TENTANG PERGESERAN MEKANISME BANTUAN SOSIAL BERSYARAT DI KECAMATAN CIPAYUNG, JAKARTA TIMUR - Gaol, Harapan Lumban (Politeknik Kesejahteraan Sosial Bandung, 2026)
The Family Hope Program (Program Keluarga Harapan – PKH) is a conditional cash transfer program designed to improve the quality of human resources among poor households through enhanced access to health, education, and social welfare services. In recent years, however, the compliance verification mechanism that constitutes the core of PKH has no longer been strictly implemented. This study aims to examine how beneficiary households continue to comply with program obligations despite the absence of formal verification, using a case study conducted in Cipayung District, East Jakarta. This study employs a qualitative descriptive approach. Data were collected through in-depth interviews, focused group discussions, field observations allowing unobtrusive observation of beneficiary behavior, and document analysis. Informants consisted of PKH administrators, social facilitators, and beneficiary households. The findings reveal that although PKH has gradually shifted toward a quasi-unconditional assistance scheme, beneficiaries’ compliance in accessing health and education services remains relatively well maintained. This condition is influenced by the internalization of program values, long-term participation experience, the mediating role of social facilitators, and the availability of adequate urban service infrastructure. The study concludes that social and normative mechanisms rooted in awareness, habituation, and moral commitment can partially substitute formal compliance verification, particularly in urban contexts. Nevertheless, the re-strengthening of monitoring and evaluation mechanisms remains essential to ensure the sustainability of PKH’s long-term objectives in improving human capital and breaking the intergenerational cycle of poverty. Keywords: Family Hope Program; conditional cash transfer; beneficiary compliance; social assistance; poverty